Vardagsteologi och tonårsmagi: Att närma sig etnografisk-teologisk forskningsmetod med hjälp av barnlitteratur - Rubenson, Karin (Tidskrift för litteraturvetenskap, 2022)
Everyday Theology and Teenage Magic: Approaching an Ethnographic-Theologic Research Method with the Aid of Children’s Literature The aim of this article is to explore how ethnographic theological method can be understood, by relating it to fantasy literature for children and young people. I am discussing children’s theological agency, focusing on relationality, hybridity and changeability, showing how children’s literature can be used to exemplify practical theological theory and method. I will primarily refer to Natalie Wigg-Stevenson’s book Ethnographic Theology: an Inquiry into the Production of Theological Knowledge and the Swedish YA novels about Engelsfors (The Circle, Fire and The Key) by Mats Strandberg and Sara Bergmark Elfgren. I am looking into questions about knowledge as contextual, embodied and relational and how uncertainty and liminality can enable, rather than hinder, action. I am using concrete examples from the novels, such as a magical book and a “body switch” episode, where the characters are magically transformed to each other, to discuss how interaction and interpretation are dependent on embodiment and context. By relating the novels to Wigg-Stevenson’s understanding of ethnographic theology, I am discussing the fluidity and uncertainty inherent in practical and ethnographic theology, children’s possibilities for agency in complex situations and children’s literature as a tool to understand and explain a research process in the field of ethnographic theology.